Penerapan Metode Multi Factor Evaluation Process (MFEP) Pada Penilaian Kinerja Kolektor Dalam Pengumpulan Dana Kredit Sepeda Motor - Ikwal Fazri (Universitas Budi Darma, 2021)
In the decision support system there are several methods used, one of which is the Multi Factor Evaluation Process (MFEP) method. The MFEP method is the method of choice in the performance appraisal decision support system at PT. Capella Multi Dana. The main tool for MFEP is to use weights or values. We must make the right judgment in assessing the performance of collectors using a collective approach to the decision-making process. The criteria in determining the collector's performance in collecting motorcycle credit funds using the MFEP method is to determine the weight of the performance factor of each collector in collecting consumer credit funds. Then each collector is evaluated and given a weight for the assessment of which collector collects more credit funds from each consumer. Then the next stage is determined the total evaluation evaluation for each collector regarding their respective performance